Job pressure and ill-health in physical education teachers: The mediating role of psychological need thwarting - Bartholomew, K.; Ntoumanis, Nikos; Cuevas, R.; Lonsdale, C. (Elsevier Science Ltd., 2014)
Drawing from self-determination theory, this study examined the interplay among PE teachers' (N = 364) self-reported perceptions of job pressure, psychological need thwarting, burnout, and somatic complaints. Structural equation modeling indicated that autonomy, competence, and relatedness need thwarting were predicted by teachers' perceptions of job pressure. In turn, the thwarting of each need was positively associated with burnout; the thwarting of the need for competence also predicted somatic complaints. Mediation analyses supported the explanatory role of need thwarting. The findings point to the understudied construct of need thwarting as a promising underlying mechanism for explaining negative health-related outcomes in teachers.